High-frequency Ventilation Does Not Provide Mortality Benefit in Comparison with Conventional Lung-protective Ventilation in Acute Respiratory Distress Syndrome: A Meta-analysis of the Randomized Controlled Trials. (April 2015) - Maitra, Souvik; Bhattacharjee, Sulagna; Khanna, Puneet; Baidya, Dalim K.
Abstract : Background: Despite implementation of lung-protective ventilation strategy, acute respiratory distress syndrome is associated with significant mortality, which necessitates the evaluation of ventilatory modes other than conventional lung-protective strategy. This meta-analysis of the randomized controlled trials has been undertaken to know whether high-frequency oscillatory ventilation (HFOV) provides any mortality benefit over conventional ventilation in adult patients with acute respiratory distress syndrome. Methods: Published randomized controlled trials comparing HFOV with conventional lung-protective ventilation in adult patients with acute respiratory distress syndrome were included in this meta-analysis. Results: A total 1, 759 patient data from seven randomized controlled trials have been analyzed here. Primary outcome of the review is in-hospital/30-day mortality and secondary outcomes are duration of intensive care unit stay, duration of mechanical ventilation, requirement of additional treatment, and complications associated with the interventions. HFOV does not offer any in-hospital/30-day mortality benefit (386 of 886 in HFOV vs. 368 of 873 in conventional ventilation; risk ratio, 0.96; 95% CI, 0.77 to 1.19; P = 0.70) over conventional ventilation. It may also prolong the duration of mechanical ventilation (mean difference, 1.18 days; 95% CI, 0.00 to 2.35 days; P = 0.05). Duration of intensive care unit stay (mean difference, 1.24 days; 95% CI, −0.08 to 2.56 days; P = 0.06) and requirement of neuromuscular blocker is similar between two treatment arm. Incidence of refractory hypoxemia is significantly less (risk ratio, 0.60; 95% CI, 0.39 to 0.93; P = 0.02) with the use of HFOV. HFOV is not associated with increased incidence of barotrauma and refractory hypotension. Conclusion: HFOV should not be used routinely in all adult patients with acute respiratory distress syndrome as primary ventilation strategy in place of conventional lung-protective ventilation. Abstract : A meta-analysis of 1, 759 patients from seven randomized controlled trials documents that the use of HFOV does not offer a mortality benefit and appears to prolong the duration of mechanical ventilation.